Peningkatan Pengetahuan Kesehatan Siswa/Siswi RA dan PAUD Abu Bakar As-Sidhiqqi tentang Manajemen Pembuangan Sampah Yang Baik - Ari Septianingtyas Purwandhini; Endang Wahyu Pudjiastutik; Deddy Kurniawan; Abdul Hadi (Indonesian Journal Publisher, 2024)
Waste is a problem that is still faced by most countries in the world. Currently, there are still many people who still throw household waste in rivers. Therefore, it is necessary to instill the intention from childhood that